Optimization of A Solar Ejector Refrigeration System in the Region of Adrar, Algeria - Derghout, Zoheir; Rouabah, Mohammed Salah (Trends in Sciences, 2022)
This study aims to simulate a solar ejector refrigeration system in the region of Adrar (27.82 N, 0.18 W). It is the first investigation of such refrigeration system in this region, the importance of this study is to benefit from the free intense solar energy for cooling and air conditioning and reduce using electrical energy produced by thermal power station which is harmful to the environment and causing warming global. It is a theoretical study using real gas equation (REFPROP database). The system is inspected for various evaporator temperatures from 0 to 30 °C and for various condenser temperatures from 25 to 50 °C. For each situation, the system is optimized by choosing the best ejector parameters and the ideal generator temperature. Different refrigerants are used as R11, R134a and R717 (ammonia). The last one is observed to be the best fluid in all the working conditions. More explicitly, the highest COPs is 0.28 when the system produces refrigeration at 30 °C and the boiler temperature is 90 °C. The COPs values are acceptable and very interesting, and it’s higher than other cities in the world like Athens, this study can be generalized in other hot regions. The examination is performed with a code written in Fortran. HIGHLIGHTS The importance of this study is to benefit from the free intense solar energy for cooling and air conditioning and reduce using electrical energy For each situation, the system is optimized by choosing the best ejector parameters and the ideal generator temperature. Different refrigerants are used as R11, R134a and R717 (ammonia). The last one is observed to be the best fluid in all the working conditions More explicitly, the highest COPs is 0.28 when the system produces refrigeration at 30 °C and the boiler temperature is 90 °C This study can be generalized in other hot regions GRAPHICAL ABSTRACT